Motorcycle Security System Using Fingerprint Authentication Based on the Internet of Things (IoT) - Sutrisno, Sutrisno; Samsumar, Lalu Delsi; Efendi, Muhamad Masjun (Ali Institute of Research and Publication, 2025)
The increasing cases of motorcycle theft in Indonesia reveal the weaknesses of conventional security systems, such as mechanical locks that are easily compromised. This condition creates a scientific gap for developing security solutions based on biometric technology and the Internet of Things (IoT). This study proposes the design of a motorcycle security system with fingerprint authentication integrated with IoT. The research method used is prototyping, which includes requirement analysis, system design, prototype development, and testing. The system is built using an ESP32 as the main controller, an AS608 fingerprint sensor for user identification, a 2-channel relay for electrical control, a solenoid lock as the physical locking mechanism, and the Blynk application for remote control via the internet, which also serves as an alternative to the fingerprint sensor in case of errors or failures. The test results demonstrate that the system can accurately recognize registered fingerprints, activate the motorcycle’s electrical system, and automatically lock and unlock the solenoid with a fast response. The Blynk application functioned effectively as both a real-time control medium and an alternative control button when the fingerprint sensor experienced errors. These findings indicate that the proposed system can enhance motorcycle security compared to conventional methods while also providing ease of access for users. However, this research is still limited to the laboratory prototype stage and has not yet been directly implemented on motorcycles under real-world conditions.